2015
DOI: 10.1093/ejcts/ezu515
|View full text |Cite
|
Sign up to set email alerts
|

Influence of visceral pleural invasion on survival in completely resected non-small-cell lung cancer

Abstract: Our results suggest that the presence of VPI, rather than the extent, has an impact on postoperative survival in patients with NSCLC who have N0 or N1 metastasis. Because very few previous studies have addressed the effects of VPI in patients with N1 disease, further re-evaluation of the prognostic impact of VPI is necessary in this subgroup of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 14 publications
2
26
2
Order By: Relevance
“…However, the prognostic value of VPI in N1 or N2 status remains controversial. Differing from Fujimoto et al and Adachi et al's conclusions, there was no significant prognostic difference of VPI status in N1 or N2 status in our study. Different results may be due to sample size and patient selection, since patients who had T3 or T4 disease (8th edition TNM staging) were excluded from our study for the concern of involving adjacent anatomic structures.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the prognostic value of VPI in N1 or N2 status remains controversial. Differing from Fujimoto et al and Adachi et al's conclusions, there was no significant prognostic difference of VPI status in N1 or N2 status in our study. Different results may be due to sample size and patient selection, since patients who had T3 or T4 disease (8th edition TNM staging) were excluded from our study for the concern of involving adjacent anatomic structures.…”
Section: Discussioncontrasting
confidence: 99%
“…The presence of VPI was reported to be an adverse prognostic factor in NSCLC, especially in N0 status . In this study cohort after PSM, the presence of VPI, increasing age, male, larger tumor size, worse features of tumor grade (the reason that undifferentiated tumor grade had a reduced hazard to the reference may be the small number of patients in this study cohort), and more advanced lymph node stage all had a negative impact on LCSS.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…As it takes time for the "indolent" GGNs to invade the surface of the visceral pleura, and the surgical intervention is usually conducted at the early stage, it is therefore uncommon to observe PL2. Adachi et al (20) reported that in tumor smaller than 3 cm, the rate of PL1 was 16.7% while the rate of PL2 was 4.4%. In a large-scale investigation by Kawase et al (21), the PL1 (C,D) although radiologically similar to the above case, there was no tumor invasion into the visceral pleura despite being histologically lepidic predominant invasive adenocarcinoma and a radiologically part-solid GGN with pleural indentation (arrow) (elastic, 40×); (E,F) a pure GGN with simply pleural attachment (arrow) was also lepidic predominant invasive adenocarcinoma with prominent VPI (elastic, 100×).…”
Section: Discussionmentioning
confidence: 99%
“…Visceral pleural invasion is one of the important prognostic factors in patients with surgically resected NSCLC, and it is included in the TNM staging system as a factor that upstages the T factor from T1 to T2 . VPI is defined as tumor extension beyond the elastic layer of the visceral pleura, regardless of invasion of the pleural surface .…”
Section: Discussionmentioning
confidence: 99%